Systematic review of surgery for persistent pediatric tracheocutaneous fistula. (13th May 2016) - Lewis, Sean; Arjomandi, Hamid; Rosenfeld, Richard
Abstract : Objectives: To compare the treatment outcomes and adverse event rates for primary closure compared to simple excision with healing by secondary intention for persistent tracheocutaneous fistula (TCF) in children. Study Design: Systematic review. Methods: Systematic review using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses reporting standards. MEDLINE, Embase, Cochrane Library, and manual search were used to identify articles. Inclusion criteria were case series or comparative studies of surgery for persistent TCF in children under age 18 years. Exclusion criteria were age 18 years or older, duplicate patient series, case series with less than two patients, or case reports. Data were pooled using random effects meta‐analysis to assess outcomes, adverse events, and comparative effectiveness. Results: We identified 14 articles with 413 patients treated with excision with primary closure and 233 patients treated with excision with closure by secondary intention. Pooled success rates were 95.7% with primary closure (95% confidence interval [CI]: 93.1% to 97.4%) and 92.7% with secondary intention (95% CI: 88.4% to 95.4%). Subcutaneous emphysema or urgent airway problems were uncommon, occurring in 3.8% and 3.6% of patients, respectively. Five studies had data suitable for comparative meta‐analysis, which showed no differences by closure technique for treatment success ( P = .480), overall complications ( P = .551), need for revision surgery ( P = .624), or the incidence of subcutaneous emphysema or pneumothorax ( P = .512), urgent airway problems ( P = .126), wound infection ( P = 1.00), or wound dehiscence or fistula ( P = .818). Conclusions: There are no differences in the rates of success or complications with surgical closure of TCF in children, whether performed by primary closure or by secondary intention. Both techniques have high success rates with a low incidence of serious complications. Laryngoscope, 127:241–246, 2017